PENYAKIT CHARCOT MARIE TOOTH ONSET LANJUT - Kenny Merryn,* Jimmi Sabirin,* Octaviani* (NEURONA, 2020)
MARIE TOOTHS DISEASE CMT IS A HEREDITARY SENSORIC MOTORIC POLINEUROPATHY LATE ONSET CMT ARE RARE REPORTED IN INDONESIA A WOMAN 48 YEARS OLD HAS NUMBNESS IN HER BOTH ARM AND LEG GRADUALLY SINCE 5 YEARS AGO FOLLOWED BY DEFORMITIES AND WEAKNESS